2018
DOI: 10.1007/s00198-018-4679-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypophosphatemia induced by denosumab in a patient with osteomalacia and tenofovir disoproxil fumarate-related acquired Fanconi syndrome

Abstract: Denosumab, a novel agent that inhibits osteoclasts, reduces the risk of fracture in patients with osteoporosis. However, worsening of hypophosphatemia and other symptoms may be induced by denosumab in patients with pre-existing hypophosphatemic osteomalacia. A 58-year-old man with hepatitis B presented with diffuse bone pain and muscle weakness. Denosumab was prescribed by the orthopedist according to documented low bone mass and spine compression fracture. After administering denosumab, the patient's bone pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…Consequently, denosumab can induce or worsen preexisting hypophosphatemia and osteomalacia in TDF‐acquired Fanconi syndrome, leading to severe bone pain and atraumatic fractures. ( 1 ) Similar effects were observed after zoledronic acid administration in a patient with undiagnosed TDF‐induced osteomalacia. In this case, a mild hypophosphatemia was already observed before the bisphosphonate administration, with a consecutive aggravation afterward accompanied by several fractures.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Consequently, denosumab can induce or worsen preexisting hypophosphatemia and osteomalacia in TDF‐acquired Fanconi syndrome, leading to severe bone pain and atraumatic fractures. ( 1 ) Similar effects were observed after zoledronic acid administration in a patient with undiagnosed TDF‐induced osteomalacia. In this case, a mild hypophosphatemia was already observed before the bisphosphonate administration, with a consecutive aggravation afterward accompanied by several fractures.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported repeatedly, that anti-resorptive treatment might lead to hypocalcemia and hypophosphatemia in patients with existing osteomalacia. Consequently, Denosumab can induce or worse pre-existing hypophosphatemia and osteomalacia in TDF acquired Fanconi syndrome, leading to severe bone pain and atraumatic fractures [1]. Similar effects were observed after zoledronic acid administration in a patient with undiagnosed TDF-induced osteomalacia.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Monitoring of the serum calcium level also is mandatory to prevent severe hypocalcemia when denosumab is initiated in all forms of osteomalacia. Very recently, there was another case report of hypophosphatemia osteomalacia secondary to Fanconi syndrome in which bone pain was worsened by administration of denosumab [15]. Unlike in these reports, we observed that 2 months after initiation of denosumab, hip and knee pain of our patient was relieved along with a decrease in serum ALP and some bone resorption markers.…”
Section: Discussioncontrasting
confidence: 71%